Do Age and Weight Bearing Films Affect Lateral Joint Space and Fibular Height Measurements in Patients with Discoid Lateral Meniscus?. Issue 7 (18th July 2016) - Milewski, Matthew David; Krochak, Ryan; Duarte, Andrew J.; Marchese, Joseph; Pace, James Lee; Broom, Alexander M.; Solomito, Matthew
Objectives: Several radiographic parameters have been associated with discoid lateral meniscus. We sought to determine the effect of age and weight bearing (WB) on radiographic parameters associated with lateral discoid menisci in pediatric patients. Methods: Radiographs of patients with arthroscopically confirmed lateral discoid meniscus were compared to age, side, sex matched individuals with confirmed normal menisci. The radiographs were measured by a pediatric orthopaedic sports medicine attending and two orthopaedic residents for the following parameters: lateral joint space width (LJSW), fibular head height (FHH), width of the distal femur (WDF), tibial spine height (TSH), cupping of the lateral tibial plateau (CLTP), and obliquity of the lateral tibial plateau (OLTP). The results of this review focus on FHH and LJSW only. Results: 68 knees with discoid lateral menisci with a mean age of 11.6 ± 3.3 (15 WB films) were compared to 67 control knees with a mean age of 11.9 ± 3.2 (15 WB films). Results indicated that there were significant differences between the discoid and control groups when comparing LJSW (8.7 ± 2.2 mm discoid compared to 7.6 ± 2.1 mm control p=0.002) and FHH (13.5 ± 4.5 mm discoid compared to 18.6 ± 3.9 mm control p<0.001). Inter-rater reliability was satisfactory for LJSW and FHH (ICC 0.635 and 0.759 respectively). WB films were noted to have better inter-rater reliability compared to NWB films for LJSW (ICC 0.729 vs 0.514 respectively) but reduced inter-rater reliability for FHH (ICC 0.625 vs 0.868 respectively). Subgroup analysis based on age was also done comparing patients under 10 years old, patients between 10-14 years old, and patients over 14 years old. The FHH measurement was significantly decreased (indicative of a high fibular head) in the discoid group in all age groups. However, LJSW was only noted to be significantly different in patients over the age of 14. Conclusion: Increased lateral joint space width and a high fibular head were associated with discoid lateral menisci and also showed satisfactory inter-rater reliability. Weightbearing films showed better inter-rater reliability for LJSW but decreased reliability for FHH. Higher fibular height was consistently seen across age groups but increased LJSW was only significantly different in the over 14 years old group. Fibular height might be a better radiographic parameter for discoid lateral meniscus evaluation across all age groups while lateral joint space may be better in older adolescent patients.